2014
DOI: 10.1007/s00429-014-0897-3
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent nicotine-induced dendrite remodeling in the nucleus accumbens is rapid, persistent, and D1-dopamine receptor dependent

Abstract: Chronic nicotine exposure during adolescence induces dendritic remodeling of medium spiny neurons (MSNs) in the nucleus accumbens (NAcc) shell. While nicotine-induced dendritic remodeling has frequently been described as persistent, the trajectory of dendrite remodeling is unknown. Specifically, no study to date has characterized the structural plasticity of dendrites in the NAcc immediately following chronic nicotine, leaving open the possibility that dendrite remodeling emerges gradually over time. Further, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 84 publications
2
18
0
Order By: Relevance
“…Overall, these papers were the first to convincingly demonstrate nicotine-induced age-related modifications of MSN dendritic morphology in the NAcc, a brain region critical for processing the reinforcing properties of drugs of abuse. Ehlinger et al (2015) recently confirmed the finding that adolescent nicotine stimulates MSN dendritic growth, found that this growth occurs after a more limited dosing period (3X weekly IP injection, 0.5 mg/kg, P28-42), and showed that the elaboration is evident immediately upon the conclusion of dosing; it does not require a prolonged postdosing incubation period. The rapidly developing proliferation is also persistent, and remains at three weeks postdosing.…”
Section: Adolescent Nicotine and Nucleus Accumbens Dendritic Morphologysupporting
confidence: 56%
See 1 more Smart Citation
“…Overall, these papers were the first to convincingly demonstrate nicotine-induced age-related modifications of MSN dendritic morphology in the NAcc, a brain region critical for processing the reinforcing properties of drugs of abuse. Ehlinger et al (2015) recently confirmed the finding that adolescent nicotine stimulates MSN dendritic growth, found that this growth occurs after a more limited dosing period (3X weekly IP injection, 0.5 mg/kg, P28-42), and showed that the elaboration is evident immediately upon the conclusion of dosing; it does not require a prolonged postdosing incubation period. The rapidly developing proliferation is also persistent, and remains at three weeks postdosing.…”
Section: Adolescent Nicotine and Nucleus Accumbens Dendritic Morphologysupporting
confidence: 56%
“…While changes in dendritic branching don't provide direct confirmation of synaptic changes, we earlier noted that all branches of NAcc MSNs in nicotine-dosed animals were densely spined ; this by definition includes the new branches induced by nicotine, although we cannot identify new branches separately in Golgi-stained tissue. Ehlinger et al (2015) recently found transient increases in spine density on MSN dendrites, and persisting increase in spine number (density × total branch length), after adolescent nicotine. We (Ehlinger et al, 2012b) also reported that, while spine density was not increased in dentate after adolescent nicotine, the estimate of total number of spines was similarly increased by increased total dendrite length.…”
Section: Adolescent Nicotine Synaptic Connectivity and Information mentioning
confidence: 96%
“…The pattern of adolescent nicotine-induced dendritic remodeling observed in the BNST in the present study is similar to results in the NAcc shell [12,6], and basolateral amygdala [2], in which the formation of new dendritic branches occurs primarily on the portion of the dendritic arbor distal to the soma. However, the 49% increase in total branch length of BNST neurons represents a more robust response than has been observed in other structures examined to date.…”
Section: Discussionsupporting
confidence: 84%
“…The pattern of dendritic remodeling observed in the BNST, in which elaboration occurs on the distal dendritic arbor, may suggest that similar mechanisms regulate nicotine-induced dendritic remodeling in each of these brain regions. Recently, [6] found that adolescent nicotine-induced dendrite remodeling in the NAcc shell is dependent on D1 dopamine receptor activity during the time of drug-exposure, that remodeling occurs rapidly following nicotine administration, and is persistent through an extended withdrawal period. Neurons within the BNST are similar to those in the NAcc in that the majority are GABAergic and classified as medium spiny neurons (MSNs) [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation